Trans-Colonial Collaboration and Slave Narrative: Mary Prince Revisited - Michelle Gadpaille (ELOPE, 2011)
In 1831 in London, two formidable women met: Mary Prince, an ex-slave from Bermuda, who had crossed the Atlantic to a qualified freedom, and Susanna Strickland, an English writer. The narrative that emerged from this meeting was The History of Mary Prince, which played a role in the fight for slave emancipation in the British Empire. Prince disappeared once the battle was won, while Strickland emigrated to Upper Canada and, as Susanna Moodie, became an often quoted 19th century Canadian writer. Prince dictated, Strickland copied, and the whole was lightly edited by Thomas Pringle, the anti-slavery publisher at whose house the meeting took place.